Kira-Kira - Kadohata, Cynthia (New York Atheneum Books for Young Readers, 2004)
Chronicles the close friendship between two Japanese- American sisters growing up in rural Georgia during the late 1950s and early 1960s, and the despair when one sister becomes terminally ill.
Keywords: Fiction; Fiction; Juvenile fiction .; Juvenile fiction; Juvenile fiction; Juvenile fiction; History -- 20th century -- Fiction; History -- 20th century -- Juvenile fiction .